Virtual Reality in Initial Teacher Education (VRITE): a reverse mentoring model of professional learning for learning leaders. Issue 1 (2nd January 2022) - Farrell, Rachel; Cowan, Pamela; Brown, Martin; Roulston, Stephen; Taggart, Sammy; Donlon, Enda; Baldwin, Mark
ABSTRACT: This small-scale design-based study describes a cyclical model of professional learning between three stakeholders in initial teacher education (ITE) namely: university-based educators (UEs), student teachers (STs) and co-operating teachers (CTs). This model promotes the development of digital learning leaders through an innovative mentoring process. This process started with university-based educators (UEs) mentoring their student teachers (STs) in the pedagogical use of Virtual Reality (VR) and the creation of re-usable learning objects (RLOs). STs were supported and encouraged to cascade this learning to their placement schools as digital learning leaders connecting the innovative practice from the university directly to their classroom practice. Through bi-directional reverse-mentoring the STs and CTs supported each other technically (with the VR) and pedagogical (through the links to the curriculum) to create additional subject-specific RLOs which the STs were able to demonstrate to the UEs on their return to university. Thus, providing the final link in the cycle of learning leaders across the triad of partners in ITE.